Economic analysis, moral philosophy, and public policy - Hausman, Daniel M., 1947-; McPherson, Michael S. (Cambridge University Press, 2006)
Economic Analysis, Moral Philosophy and Public Policy shows through accessible argument and numerous examples how understanding moral philosophy can improve economic analysis, how moral philosophy can benefit from economists' analytical tools, and how economic analysis and moral philosophy together can inform public policy.